Healthcare resource use and costs of diabetic macular oedema for patients with antivascular endothelial growth factor versus a dexamethasone intravitreal implant in Korea: a population-based study - SeungJin Bae; HyunJeong Cho; Kyung Seek Choi; Joo Yong Lee; Donghwan Lee; Nam-Kyong Choi; YouKyung Lee (BMJ Open)
Objectives To estimate the costs and healthcare resources of patients with diabetic macular oedema (DME) who received intravitreal antivascular endothelial growth factor (anti-VEGF) agents or a dexamethasone intravitreal implant (DEX-implant) in Korea.Design Retrospective cohort study.Setting The Korean National Health Insurance claim data from 1 January 2015 to 30 June 2017 were retrieved from the Health Insurance Review and Assessment Service.Participants Adult patients with DME who were diagnosed with diabetic retinopathy or DME and received ranibizumab, aflibercept or a DEX-implant in conjunction with intravitreal injection were included. Patients whose primary diagnoses were age-related macular degeneration or retinal vein occlusion were excluded.Main outcome measures Healthcare resource utilisation and costs related to DME in the 12-month postindex period.Results During the study period, 182 patients and 414 patients were identified in the anti-VEGF and DEX-implant groups, respectively, and there was no significant difference in the demographic characteristics between the two groups. The outpatient eye care-related medical costs were US$3002.33 for the anti-VEGF group vs US$2250.35 for the DEX-implant group (p<0.0001). After adjusting the relevant covariates based on the generalised linear model, the estimated outpatient eye care-related medical costs were 33% higher in the anti-VEGF group than in the DEX-implant group (p<0.0001, 95% CI 22% to 45%). The utilisation pattern of the two groups showed no significant difference except for the number of intravitreal injections, which was higher in the anti-VEGF group (2.69±2.29) than in the DEX-implant group (2.09±1.37, p<0.001).Conclusion The average annual eye-related medical cost of the DEX-implant group was significantly lower than that of the anti-VEGF group during the study period, which was mainly due to decreased utilisation of eye care-related injections. Further long-term studies are needed.